Analisis Bisnis Telur Asin dengan Metode SWOT dan Fish bone di UMKM Desa Wonosari - Hurun 'in; Samsudin Bahari (Fakultas Teknik dan Rekayasa, 2024)
Wonosari Village MSMEs are Wonosari MSMEs that produce high quality salted eggs. However, MSME sales are unstable. The problems that occur in the MSMEs NR Wonosari Village district include a few marketing areas, small capital, the quality of eggshells that are easily cracked, problems of low productivity in producing, and difficulties in finding suppliers. The external problems are the lack of guidance and supervision from local governments on the existence of the salted egg industry. Due to the unstable state of MSME sales results, a study was conducted